IMPLEMENTASI APLIKASI KEHADIRAN PERKULIAHAN DI KELAS MENGGUNAKAN PEMBACA RFID PADA E-KTP - Muhamad Akbar; Irman Effendy (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
This research was conducted to help the process of teaching and learning in the classroom by utilizing information technology by utilizing e-KTP card reader with class attendance application. E-ID card now has a chip that can be used and owned by students. In this study built an application that can read the chip in e-ID card, then used as the data as a student class counter. The research method used is descriptive qualitative method with design method with iterative design method. In this process is also sought chip specifications that are connected to the e-ID card to more easily find the type of card reader connected to the application. Research results can help lecturers and students in the process of recording in the classroom, and the university can monitor students and lecturers look effectively and efficiently. This application is also expected to be adopted to be applied to other relevant fields in e-ID card utilization